Electric-field-driven non-volatile multi-state switching of individual skyrmions in a multiferroic heterostructure - Yadong Wang (Nature Portfolio, 2020)
Spin-polarized current manipulation of magnetic skyrmions is energy consuming. Here, the authors achieve an electric-field manipulation of individual skyrmions in a nanostructured ferromagnetic/ferroelectrical heterostructure at room temperature via an inverse magneto-mechanical effect.